2018
DOI: 10.1136/bmjopen-2018-025333
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for the insight study: a randomised controlled trial of single-dose tocilizumab in patients with depression and low-grade inflammation

Abstract: IntroductionObservational studies indicate a potentially causal role for interleukin 6 (IL-6), a proinflammatory cytokine, in pathogenesis of depression, but interventional studies based on patients with depression have not been conducted. Tocilizumab, anti-inflammatory drug, is a humanised monoclonal antibody that inhibits IL-6 signalling and is licensed in the UK for treatment of rheumatoid arthritis. The main objectives of this study are to test whether IL-6 contributes to the pathogenesis of depression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 47 publications
0
38
0
Order By: Relevance
“…Camara et al [44] reported that centrally administered etanercept improved anxiety-like behavior in mice. Khandaker et al [23] presented a protocol of a trial initiated in 2018, where behavioral and cognitive measures will be evaluated in tocilizumabtreated patients. In addition to pharmacotherapy, tailored cognitive behavioral therapy introduced in early RA was found to be beneficial in various studies [45,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Camara et al [44] reported that centrally administered etanercept improved anxiety-like behavior in mice. Khandaker et al [23] presented a protocol of a trial initiated in 2018, where behavioral and cognitive measures will be evaluated in tocilizumabtreated patients. In addition to pharmacotherapy, tailored cognitive behavioral therapy introduced in early RA was found to be beneficial in various studies [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Methotrexate (MTX) and corticosteroids have been associated with cognitive impairment [9,20,21]. As inflammation is involved in cognitive dysfunction in RA, the control of disease activity may be beneficial for the patients [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…With evidence for pro-inflammatory cytokines being elevated in depression, it is of no surprise that targeted anticytokine therapy is of interest in the primary management of MDD. Clinicaltrials.gov lists an active study for tocilizumab (IL-6 inhibitor) in treatment-refractory MDD, and the trial protocol for the insight study, which will assess the effect of a single intravenous infusion of tocilizumab on somatic symptoms score, has been published [36]. JAK/STAT modulation is also of theoretical benefit, as this pathway is involved in neurogenesis, synaptic plasticity, gliogenesis and microglial activation, and also with some antidepressants having a mechanism of action mediated by JAK/STAT-dependent mechanisms [5 ▪ ].…”
Section: Effects Of Targeted Therapy For Rheumatoid Arthritis On Deprmentioning
confidence: 99%
“…100 A proofof-concept double blind RCT of the anti-IL-6R mAb tocilizumab in patients with depression is underway, with subjects selected based upon evidence of inflammation and inflammation-related symptoms. 101 Turning to data from patients with AS, the mood improving effects of infliximab is consistent with a potentially shared role of inflammation in pathogenesis of depression, AS and other chronic inflammatory physical illness. 102 Sickness behaviour, a response to inflammation in autoimmune disease or infection, is characterised by fatigue, sleep problems, anhedonia, reduced appetite, concentration and motivation, which are also typical symptoms of depression.…”
Section: Role Of Disease-related Factorsmentioning
confidence: 82%
“… 100 A proof-of-concept double blind RCT of the anti-IL-6R mAb tocilizumab in patients with depression is underway, with subjects selected based upon evidence of inflammation and inflammation-related symptoms. 101 …”
Section: Potential Mechanisms Of Depression In As or Psa Patientsmentioning
confidence: 99%